2012
DOI: 10.1007/s10461-012-0151-z
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Mobile Health Unit for Rural HIV Clinical Trial Enrollment and Participation

Abstract: Few rural minorities participate in HIV clinical trials. Mobile health units (MHUs) may be one strategy to increase participation. We explored community perceptions of MHU acceptability to increase clinical trial participation for rural minorities living with HIV/AIDS. We conducted 11 focus groups (service providers and community leaders) and 35 interviews (people living with HIV/AIDS). Responses were analyzed using constant comparative and content analysis techniques. Acceptable MHU use included maintaining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Of the 108 studies, 48 studies (44.4%) conducted stakeholder engagement in high‐income countries 5, 23, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. In contrast, fewer studies conducted stakeholder engagement in middle‐ (30 studies; 27.8%) 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93,...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 108 studies, 48 studies (44.4%) conducted stakeholder engagement in high‐income countries 5, 23, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70. In contrast, fewer studies conducted stakeholder engagement in middle‐ (30 studies; 27.8%) 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93,...…”
Section: Resultsmentioning
confidence: 99%
“…All five of these studies were published from the year 2005 onward, suggesting more recent diversification of stakeholder engagement methods. Additionally, many studies used a combination of both individual and group methods for stakeholder engagement; for example, 19 studies (17.6%) paired focus group discussions with stakeholder interviews [5,16,27,32,33,79,82,89,90,96,98,100,101,106,108,109,116,125,128]. Table 2 presents our analysis of the types of stakeholders engaged throughout all studies reviewed.…”
Section: Methods Of Stakeholder Engagement For Hiv Clinical Trialsmentioning
confidence: 99%
“…Individuals have little or no sense of ownership over clinical trials as they may have a false belief that the science is beyond their scope of understanding and the practicalities of vaccine development does not necessarily involve them [ 11 ]. To enrol such a group of people into a clinical trial, especially a HIV vaccine clinical trial which is a first in humans, there is need to elucidate the motivators that may be required for volunteer enrolment, retention and follow-up in a clinical study [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…77,78 This was seen in a number of the qualitative studies in which community and the need for trust of those doing the research and engagement with their community were reported. [52][53][54][55][56][57][58]63 This coincides with the one large randomized control trial (RCT) aimed at increasing racial and ethnic participation in clinical trials 70 that used community peer educators to deliver educational activities. More interventions like this should be used by clinical sites to increase participation in these harderto-reach groups.…”
Section: Discussionmentioning
confidence: 81%
“…Of these, nine were cross-sectional surveys 36,[44][45][46][47][48][49][50][51] and seven were qualitative assessments. [52][53][54][55][56][57][58] Another eight studies addressed factors to participating specifically in a vaccine trial (four cross-sectional, [59][60][61][62] four qualitative [63][64][65][66] ). The remaining studies reported on small pilot or full randomized behavioral interventions aimed at increasing intention to or actual participation in a clinical trial.…”
Section: Resultsmentioning
confidence: 99%